2020
DOI: 10.1088/1742-6596/1465/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of gastropoda in meru betiri national park

Abstract: National Park plays important role in maintaining natural ecosystems such as freshwater ecosystems. Meru Betiri National Park is loacted in southern East Java, it covers two regencies, Banyuwangi and Jember. A recent survey was carried out in two resorts, Bandealit and Andongrejo, to study the diversity of freshwater gastropoda. We had collected 86 specimens which consisted of five families, seven genera, and nine species. Seven species were found from Andongrejo and four species were found from Bandealit. Riv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…With thorns in the shell, it can make it difficult for snail predators such as fish to eat it. Clithon found in several habitats such as large rocky substrates, sandy, and soil that have a water temperature of 26°C, a water pH of 7.4 (Suratno et al 2020). Clithon bicolor is a type of snail that has the most extensive distribution, which can be found in 4 of 6 provinces in Java, and Banten Province has the highest number of snail species, 10 species, and then West Java has 9 species (Suratno et al 2020).…”
Section: Family Of Neritidaementioning
confidence: 99%
See 1 more Smart Citation
“…With thorns in the shell, it can make it difficult for snail predators such as fish to eat it. Clithon found in several habitats such as large rocky substrates, sandy, and soil that have a water temperature of 26°C, a water pH of 7.4 (Suratno et al 2020). Clithon bicolor is a type of snail that has the most extensive distribution, which can be found in 4 of 6 provinces in Java, and Banten Province has the highest number of snail species, 10 species, and then West Java has 9 species (Suratno et al 2020).…”
Section: Family Of Neritidaementioning
confidence: 99%
“…Clithon found in several habitats such as large rocky substrates, sandy, and soil that have a water temperature of 26°C, a water pH of 7.4 (Suratno et al 2020). Clithon bicolor is a type of snail that has the most extensive distribution, which can be found in 4 of 6 provinces in Java, and Banten Province has the highest number of snail species, 10 species, and then West Java has 9 species (Suratno et al 2020). Young snails that live in calm waters, sometimes their shells have thorns, whereas, in adult snails that live in fast-flowing waters, these thorns can reduce or disappear.…”
Section: Family Of Neritidaementioning
confidence: 99%
“…The habitats of this species are rivers or lakes with calm or swift currents. Previous research found that Sulcospira testudinaria was present in the Cikeruh River [Lutfi et al, 2020], Code River [Hellen et al, 2020], Meru Betiri National Park [Suratno et al, 2020], Gunung Kidul [Isnaningsih and Listiawan, 2010], and the Brantas River [Febbyanto et al, 2015]. This species was used as a bioindicator for aquatic environmental health [Hertika et al, 2021], and was used to measure the results of efforts to reduce levels of organic matter in aquaculture wastewater [Lailiyah et al, 2021].…”
Section: Introductionmentioning
confidence: 99%